2021
DOI: 10.37729/radiasi.v14i1.897
|View full text |Cite
|
Sign up to set email alerts
|

Uji Perbandingan antara Virtual Lab dengan Real Lab pada Hukum Archimedes dengan penggunaan HOT-LAB

Abstract: Pandemi Covid-19 menjadi kendala dalam melaksanakan kegiatan eksperiman secara langsung. Namun demikian dapat diatasi dengan percobaan interaktif menggunakan Virtual Lab yang sistematis dan memiliki akurasi yang baik. Dalam penelitian ini dilakukan kegiatan praktikum secara virtual menggunakan simulasi PhET yang dipadukan dengan HOT-LAB guna mengetahui perbandingan antara virtual lab dengan real lab yang dipadu dengan HOT-Lab. Metode yang digunakan adalah dengan uji perbandingan dari hasil analisis data percob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In his work, Schiebener [[17]] shows a linear result that the refractive index value for each color increases steadily with increasing wavelength. There are no changes that vary in the use of the virtual lab, because virtual Lab is a lab activity that has been programmed using measurements made by a real lab[ [18]]. Figure 4 shows the value of the increase in the refractive index with wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…In his work, Schiebener [[17]] shows a linear result that the refractive index value for each color increases steadily with increasing wavelength. There are no changes that vary in the use of the virtual lab, because virtual Lab is a lab activity that has been programmed using measurements made by a real lab[ [18]]. Figure 4 shows the value of the increase in the refractive index with wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…The high result of argumentation skills in virtual laboratory activities is because virtual laboratories are considered easier to use and can also be efficient time (Potkonjak et al, 2016). In addition, previous research revealed that using a virtual laboratory can make students more quickly find evidence to meet evidence in argumentation skills (Malik & Ubaidillah, 2021;Putra et al, 2021). Other previous studies also revealed that using a real laboratory will take more time than using a virtual laboratory, so when students do backing, it will be easier to do virtual laboratory activities than real laboratory activities (Roviati et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The media allows students to carry out practicum activities without having to go to the actual laboratory room, so it can be a solution to the demands of using technology in learning. In its use, the Mobile Geography Virtual Laboratory is more flexible in terms of time and location, the practicum is safer to do, and the results are fast and can be repeated directly [3]; [22]; [20]. The disadvantage of the Mobile Geography Virtual Laboratory media is that the material developed is still limited, so it is recommended to be developed in other sub-materials that are still related to practicum activities.…”
Section: Fig 8 Evaluation Menu Of the Applicationmentioning
confidence: 99%